2006
DOI: 10.1152/ajpheart.00369.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of right ventricular function after monocrotaline-induced pulmonary hypertension in the intact rat

Abstract: We characterized hemodynamics and systolic and diastolic right ventricular (RV) function in relation to structural changes in the rat model of monocrotaline (MCT)-induced pulmonary hypertension. Rats were treated with MCT at 30 mg/kg body wt (MCT30, n = 15) and 80 mg/kg body wt (MCT80, n = 16) to induce compensated RV hypertrophy and RV failure, respectively. Saline-treated rats served as control (Cont, n = 13). After 4 wk, a pressure-conductance catheter was introduced into the RV to assess pressure-volume re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
96
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 48 publications
26
96
0
3
Order By: Relevance
“…This concept has been confirmed in aortic banding models (9,36), but it is unclear whether it is applicable to the RV. Previous studies, both experimental and clinical, suggested that in the proximal-type pressure overload, increased contractility rather than Frank-Starling mechanism characterizes the RV response (15,30), whereas in the peripheral-type pressure overload, the RV response is limited to the Frank-Starling mechanism and does not increase contractility (21). By direct comparison, however, this study shows that in both proximal-and peripheral-type pressure overload the RV response uses the Frank-Starling mechanism, but additionally depends on increased contractility for maintaining stroke volume.…”
Section: The Rv Responds To Chronic Pressure Overload With Both Frankmentioning
confidence: 98%
“…This concept has been confirmed in aortic banding models (9,36), but it is unclear whether it is applicable to the RV. Previous studies, both experimental and clinical, suggested that in the proximal-type pressure overload, increased contractility rather than Frank-Starling mechanism characterizes the RV response (15,30), whereas in the peripheral-type pressure overload, the RV response is limited to the Frank-Starling mechanism and does not increase contractility (21). By direct comparison, however, this study shows that in both proximal-and peripheral-type pressure overload the RV response uses the Frank-Starling mechanism, but additionally depends on increased contractility for maintaining stroke volume.…”
Section: The Rv Responds To Chronic Pressure Overload With Both Frankmentioning
confidence: 98%
“…A repeat cardiac catheterization after six months of therapy showed a mild decrease in PAP to 64/39 mmHg, and an increase in cardiac index to 2.6 l/min/m 2 . (Hessel et al, 2006). MCT-induced PH varies among strains and species of animals.…”
Section: Case Studymentioning
confidence: 99%
“…Many experimental animal models of PAH exist and this includes monocrotaline (MCT)-induced and chronic hypoxiainduced rats (9)(10)(11). Although the precise mechanism by which MCT leads to PAH is unknown, the MCT-induced PAH model is a mainstay in evaluating experiments of new therapeutic interventions.…”
mentioning
confidence: 99%